Ligustrazine Attenuates Myocardial Injury Induced by Coronary Microembolization in Rats by Activating the PI3K/Akt Pathway - Su, Qiang (Oxid Med Cell Longev, 2019)
BACKGROUND/AIMS: Coronary microembolization- (CME-) induced myocardial injury and progressive cardiac dysfunction are mainly caused due to CME-induced myocardial local inflammatory response and myocardial apoptosis. Ligustrazine plays an important protective role in multiple cardiovascular diseases, but its role and the protection mechanism in CME is unclear. This study hypothesized that ligustrazine attenuates CME-induced myocardial injury in rats. This study also explored the mechanism underlying this attenuation. METHODS: Forty SD rats were randomly divided into CME group, ligustrazine group, ligustrazine+LY294002 (ligustrazine+LY) group, and sham group (ten rats in each). In each group, the cardiac function, apoptotic index, serum c-troponin I (cTnI) level, inflammation [interleukin-1β (IL-1β) and tumor necrosis factor-alpha (TNF-α)], and oxidative stress [nitric oxide (NO), superoxide dismutase (SOD), and malondialdehyde (MDA)] were determined. Western blotting was used to detect the proteins which are present in the PI3K/Akt pathway. RESULTS: Ligustrazine improved cardiac dysfunction induced by CME, increased serum NO and SOD activities, and decreased the serum level in IL-1β, MDA, cTnI, and TNF-α. Moreover, ligustrazine inhibited myocardial apoptosis, which is perhaps caused by the upregulated Bcl-2, the downregulated cleaved caspase-3 and Bax, and the increased protein level in endothelial nitric oxide synthase and phosphorylated Akt. These effects, however, were reduced if ligustrazine was coadministered with LY294002. CONCLUSIONS: Ligustrazine attenuates CME-induced myocardial injury. The effects associated with this attenuation may be achieved by activating the myocardium PI3K/Akt signaling pathway.